2014
DOI: 10.1371/journal.pone.0103940
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Emotions and Coping: The Benefits of Secondary Emotions

Abstract: The existing empirical literature suggests that during difficult situations, the concurrent experience of positive and negative affects may be ideal for ensuring successful adaptation and well-being. However, different patterns of mixed emotions may have different adaptive consequences. The present research tested the proposition that experiencing a pattern of secondary mixed emotion (i.e., secondary emotion that embrace both positive and negative affects) more greatly promotes adaptive coping than experiencin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 57 publications
3
41
0
1
Order By: Relevance
“…Being able to represent such future positive feelings motivates people to continue with the actions that are necessary to obtain the goal despite their negative feeling. Along these lines, ambivalent affect can also provide a sense of comfort, promoting both psychological and physiological resilience in the face of negative mood or the traumatic elements of memories (Braniecka, Trzebinska, Dowgiert, & Wytykowska, 2014; Larsen, Hemenover, Norris, & Cacioppo, 2003). This effect that has been well documented for nostalgia (Matsunaga et al, 2013; Newman, Sachs, Stone, & Schwarz, 2020; Routledge, Wildschut, Sedikides, & Juhl, 2013; Zhou, Sedikides, Wildschut, & Gao, 2008; Zhou, Wildschut, Sedikides, Chen, & Vingerhoets, 2012).…”
Section: Conflict Is Critical To the Function Of Ambivalent Affectmentioning
confidence: 99%
“…Being able to represent such future positive feelings motivates people to continue with the actions that are necessary to obtain the goal despite their negative feeling. Along these lines, ambivalent affect can also provide a sense of comfort, promoting both psychological and physiological resilience in the face of negative mood or the traumatic elements of memories (Braniecka, Trzebinska, Dowgiert, & Wytykowska, 2014; Larsen, Hemenover, Norris, & Cacioppo, 2003). This effect that has been well documented for nostalgia (Matsunaga et al, 2013; Newman, Sachs, Stone, & Schwarz, 2020; Routledge, Wildschut, Sedikides, & Juhl, 2013; Zhou, Sedikides, Wildschut, & Gao, 2008; Zhou, Wildschut, Sedikides, Chen, & Vingerhoets, 2012).…”
Section: Conflict Is Critical To the Function Of Ambivalent Affectmentioning
confidence: 99%
“…It has been shown that induced fear leads to higher levels of anger, and induced sadness leads to lower levels of aggression (Zhan et al, 2015 ). Additionally, a study on the function of mixed emotions (i.e., two opposing emotions) found that the experience of secondary mixed emotions promotes adaptive coping in stressful situations by lowering the perceived negativity of an adverse event (Davydov et al, 2011 ), and by supporting solution-oriented actions to handle adversity (Braniecka et al, 2014 ). For example, concurrent negative emotions in victims of stalking have been found to lead to the use of more effective coping strategies (Ngo and Paternoster, 2013 ).…”
Section: The Role Of Co-occurring Emotions and Personality Traits In mentioning
confidence: 99%
“…For example, some researchers discuss how feeling one emotion (often negative) followed rapidly by a positive emotion is more effective for regulating distress than feeling emotions of the same valence simultaneously [22]. Yet, even momentary sampling studies may fail to differentiate among these types of experiences, as it is difficult to capture the small but critical time sequences of these mixed experiences.…”
Section: Summary and Recommendations For Future Researchmentioning
confidence: 99%